Analisis Peran Orang Tua dalam Pendampingan Kemampuan Membaca Anak Usia SD - Anggraini Wahyucahyani; Renata Eka Sayuti; Siti Nurkholipah; Rian Damariswara (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2023)
This study aims to improve the reading ability of school students elementary school, where we all must have known that elementary school students class low, of course, not all of them can or are not fluent in reading, so they like it or not want parents to play an active role in children's education to improve abilities read their own children. But in reality there are still many parents who are busy with their respective jobs so that the activity of guiding children learning at home is not paid enough attention and there are also parents who do not understand their children's learning materials. The purpose of this research is to examine literature study regarding the effect of parental guidance on ability reading for low grade students. The data collection technique used was interviews with students' parents. The data analysis technique was carried out descriptively. The results of this study indicate parental guidance in reading ability their children can be seen from the way the parents make a schedule of learning activities at home well, create a pleasant atmosphere when guiding their children learning, by bringing in tutors when parents are less able to teach their children to read, giving them attention and always setting aside time to guide their children learn when their parents are busy working, and provide children with learning facilities and give them an award when their child's learning achievement increases, namely by giving applause, praise or you can give it a gift so that the child feels proud and becomes active for it Study. The conclusion of this study is parental guidance is good and right will have a good impact on children, in addition to needing guidance from teachers in children's schools also need guidance from their respective parents when at home.